Apa Yang Mendorong Keberhasilan Performa Menembak Dalam Petanque? Tinjauan Sistematis Tentang Faktor Biomekanik, Psikologis, Teknis, Dan Pengalaman Kompetitif - Rully Effendi; Boby Helmi; Liliana Puspa Sari; Andra Rizky Putra (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Background. Shooting performance is a crucial determinant of success in petanque, often determining competition outcomes. Although numerous studies have examined shooting-related variables, the available evidence remains scattered across biomechanical, psychological, and technical perspectives, with no comprehensive synthesis identifying dominant performance drivers. Objectives. This systematic review aims to critically synthesize and evaluate scientific evidence on factors driving successful shooting performance in petanque, emphasizing biomechanical, psychological, and technical determinants, while identifying dominant factors and research gaps. Methods. Following PRISMA guidelines, a systematic literature search was conducted in Scopus, Web of Science, PubMed, and Google Scholar. Peer-reviewed studies published between 2022 and 2025 were screened using predefined inclusion and exclusion criteria. A total of 15 studies met the eligibility criteria and were included for qualitative synthesis. Data were extracted and analyzed to categorize performance determinants and assess their relative dominance based on frequency, methodological rigor, and reported impact. Results. This synthesis revealed four key domains influencing shooting performance: biomechanical factors (e.g., arm kinematics, release angle, grip stability, and postural balance), psychological factors (e.g., concentration, anxiety regulation, and competition confidence), technical factors (e.g., shooting technique, execution consistency, and tactical shot selection), and training and competition experience. Biomechanical consistency, psychological regulation, and competition experience were identified as the most dominant determinants, consistently associated with higher shooting accuracy across performance levels. However, heterogeneity in study designs, outcome measures, and skill classifications limits comparisons between studies. Conclusions. Successful shooting performance in petanque is driven by a multidimensional, interactive set of biomechanical, psychological, and technical factors. This review offers a new integrative framework that consolidates fragmented evidence and highlights the urgent need for standardized performance metrics and interdisciplinary research models. The findings provide evidence-based insights for coaches, athletes, and sport scientists to optimize shooting training and inform future high-quality research in petanque performance analysis.